Life cycle assessment of an integrated solid waste management system in Johor Bahru - Othman, Siti Nadzirah (2013)
The disposal of municipal solid wastes in landfill resulted in significant emissions of greenhouse gases (GHGs), predominantly methane (CH4) and causes green house effect leading to global warming. The aim of this study is to assess the environmental impacts of municipal solid waste management in Johor Bahru, Malaysia. It is also aimed at reducing the GHGs emission from the related wastedisposal activities based on several scenarios by utilizing the concept of integrated solid waste management (ISWM). This approach has been applied to optimize the management of the wastes with the main targets of GHGs emissions reduction and its impacts to the environment. In this proposed scenarios, wastes were being fractioned for different waste management options which include source separation, recycling, composting, incineration and landfilling. Subsequently, comparison of the existing and alternatives wastes management scenarios was performed based on their respective impacts to the environment via cradle-to-grave approach known as life cycle assessment (LCA). Scenario 1 is an integrated system which involves recycling, composting, incineration and landfill. Meanwhile, only three treatments involved in scenario 2 (composting, incineration, landfill) and scenario 3 (recycling, incineration, landfill). Scenario 4 is the current situation which involve recycle and landfill. Even though scenario 4 shows an emission of 2.04 kg CO2-eq of CH4 and 31.63 kg CO2-eq of carbon dioxide but by taking integrated system into account, scenario 1 gave less impact compared to others (scenario 2; 1404.99 kg CO2-eq and scenario 3; 1837.64 kg CO2-eq) with emission of 10.59 kg CO2-eq and 1292.7 kg CO2-eq for CH4 and CO2 respectively. ISWM system, with a combination all treatments of recycling, composting, incineration and landfill (scenario 4) has shown best result in general and less emissions compared to the others. A combined facility or integrated solid waste management would be ideal for Johor Bahru.